New role for penicillin acylases: degradation of acyl homoserine lactone quorum sensing signals by Kluyvera citrophila penicillin G acylase - Mukherji, Ruchira; Varshney, Nishant Kumar; Panigrahi, Priyabrata; Suresh, C. G.; Prabhune, Asmita (Enzyme and Microbial Technology, 2014)
Use of penicillin acylases for the production of semi-synthetic penicillins is well-known. Escherichia coli penicillin G acylase (EcPGA) has been extensively used for this purpose; however, Kluyvera citrophila penicillin G acylase (KcPGA) is assumed to be a better substitute, owing to its increased resilience to extreme pH conditions and ease of immobilization. In the present article we report a new dimension for the amidase activity of KcPGA by demonstrating its ability to cleave bacterial quorum sensing signal molecules, acyl homoserine lactones (AHL) with acyl chain length of 6-8 with or without oxo-substitution at third carbon position. Initial evidence of AHL degrading capability of KcPGA was obtained using CV026 based bioassay method. Kinetic studies performed at pH 8.0 and 50 degrees C revealed 3-oxo-C6 HSL to be the best substrate for the enzyme with V-max and K-m values of 21.37+0.85 mM/h/mg of protein and 0.1+0.01 mM, respectively. C6 HSL was found to be the second best substrate with V-max. and K-m value of 10.06+0.27 mM/h/mg of protein and 0.28+0.02 mM, respectively. Molecular modeling and docking studies performed on the active site of the enzyme support these findings by showing the fitting of AHLs perfectly within the hydrophobic pocket of the enzyme active site. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Acyl homoserine lactones; CV026; KcPGA; Quorum quenching

New yeast isolate Pichia caribbica synthesizes xylolipid biosurfactant with enhanced functionality - Joshi-Navare, Kasturi; Singh, Pradeep Kumar; Prabhune, Asmita (European Journal of Lipid Science and Technology, 2014)
Sophorolipids (SL) belong to a class of glycolipidic biosurfactants suitable for a wide range of applications. The structural diversity in SL gives rise to variation in physicochemical and biological properties. To achieve the less explored head group diversity in sophorolipid structure, a new xylose fermenting yeast Pichia caribbica has been employed for biosurfactant production. The media and fermentation parameters have been optimized to achieve maximum yield of 7.48 g/L. The physicochemical properties of the xylolipid biosurfactant have been assessed. It reduced the surface tension of distilled water from 70 to 35.9 mN/m with the low critical micellar concentration (CMC) 1.0 mg/L as compared to typical SL (reported CMC range 40-100 mg/L). Structural characterization was done using FTIR and HR-MS to identify the structure. 17-L-[(beta-D-xylopyranosyl)-oxy]-Delta 9-heptadecanoic acid correlated to m/z 415 majorly constituted the product. Control experiment was performed in which glucose was provided as the hydrophilic carbon. This product was also subjected to HR-MS analysis to determine its chemical nature and found to be different from xylolipid. Presence of xylose as head group was anticipated to give altered physicochemical and biological activities and indeed a low CMC value and better inhibitory action was demonstrated against Staphylococcus aureus. Practical applications: Sophorolipids produced by microbial sources have several advantageous properties over commercial petroleum-based surfactants including biodegradability, environmentally friendly nature, and low toxicity. Here, we have attempted to modify the hydrophilic head group by incorporating xylose in place of glucose. This molecule will also behave differently in response to different stimuli. Stimuli-responsive surfactants are a class of compounds with applications in stabilization of emulsions, suspensions or foams, drug encapsulation and delivery, hard-surface cleaning, personal care applications.
Keywords: Antibacterial action; Critical micelle concentration; Pichia caribbica; Sophorolipid; Xylolipid

Novel glycolipids synthesized using plant essential oils and their application in quorum sensing inhibition and as antibiofilm agents - Mukherji, Ruchira; Prabhune, Asmita (Scientific World Journal, 2014)
Essential oils (EOs) form an important part of traditional medicine so their anti-microbial and, in the recent past, antiquorum sensing activity has been well studied. However it is likely that due to their hydrophobic nature and reduced solubility in aqueous environments full potential of their activity cannot be realized. hence it is only rational to formulate a process to make these molecules more polar in nature. The present paper reports synthesis of sophorolipids using 12 different essential oils as substrates, thus providing surfactant-like properties to these EOs. The synthesis protocol makes the use of Candida bombicola ATCC 22214 as producer organism. The production process required 7 days of incubation at 28 degrees C and 180 rpm. Preliminary characterization of the synthesized essential oil sophorolipids (EOSLs) was performed using thin layer chromatography (TLC) and Fourier transform infrared spectroscopy (FTIR). Additionally, essential oils that were incapable of mediating quorum sensing inhibition (QSI) on their own became potent quorum sensing inhibitors upon conversion into their corresponding EOSLs. Antibiofilm potential of these EOSLs was also demonstrated using V. cholerae as test organism. Use of essential oils as substrates for glycolipid synthesis has not been attempted previously, and hence this is the first report.

New class of bacterial quorum sensing antagonists: glycomonoterpenols synthesized using linalool and alpha terpineol - Mukherji, Ruchira; Prabhune, Asmita (World Journal of Microbiology & Biotechnology, 2015)
With increasing burden of antibiotic resistant microorganism search for newer drug targets and potent drug molecules is a never ending scenario. Quorum sensing (QS), the phenomenon of bacterial cross-talk, is one such target that has captured the attention of many and has been touted as the future of new age antimicrobials. Quorum sensing has the potential to regulate a plethora of bacterial virulence phenotypes and search of molecules with powerful quorum sensing inhibitory (QSI) capacity are underway. Monoterpene alcohols like linalool and alpha terpineol have been shown to possess antimicrobial and anti-biofilm activity. However in this article we attempt to bring forth a new class of compounds, glycomonoterpenols, derived from monoterpenoids alcohols. These glycomonoterpenols have been synthesized using Candida bombicola ATCC 22214 by feeding the cells with linalool and alpha terpineol respectively as substrates in 10 % glucose, production medium. The advantage of these molecules over their parent compound is their additional surfactant like property, increased solubility and enhanced QSI potential. A variety of gram-negative bacteria capable of elaborating quorum sensing mediated phenotypes have been selected and both these glycoterpenoid derivatives have been shown to possess strong anti-QS activity.
Keywords: Alpha-terpineol; Glycomonoterpenols; Linalool; Pseudomonas aeruginosa; Quorum sensing inhibition